REFLECTIVE LEARNING IN CHILDBIRTH CARE TO IMPROVE SELF-CONFIDENCE OF MIDWIFERY STUDENTS - Lola Noviani Fadilah; Farid Husin; Juntika Nurihsan; Tria Giri Ramdani (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: Childbirth care is the core competency of a midwife which is found in midwifery education. Midwifery students must be equipped with the competencies. Self-confidence is an internal factor affecting the professional knowledge and competence of midwives. Low self-confidence shows in the practice of childbirth care thus the condition can be an indicator of the performance of a less-competent midwife in the future. Practice learning methods that support increased confidence should direct students to self-study based on experience so that it can solve the problem. Knowing the advantage of this method, it is valuable if reflective learning is implemented to improve self-confidence. The study aimed to analyse the influence of reflective learning on childbirth care practice for the improvement of student confidence.Methods: This research employed a quasi-experimental control group design, involving all midwifery students of semester IV at midwifery department that divided into treatment and control groups. The treatment is the implementation of reflective learning in laboratory and clinical practice. The confidence score was obtained by using questionnaires before and after treatment. Analysis of the characteristic data and pre-test with normal distribution using an unpaired T test. While the post-test  and percent increased score were not distributed normally, therefore Mann-Whitney U was tested.Results: It was revealed that there was no difference in the characteristics of respondents and pre-tests (p > 0.05). There were significant differences in post-test and percent increase (P < 0.05). Conclusion: Reflective learning can improve students’ confidence in childbirth care. Keywords: reflective learning, confidence, childbirth care.